Environmental contamination of heavy metals in some dried fish of coastal regions of Bangladesh - Akter, Suny; Fardous, Zeenath; Aktar, Jesmin; Rahman, Md Abdur; Chowdhury, Muhammed Alamgir Zaman; Sarkar, Shilpi; Billah, Md Baki (Bangladesh Journal of Zoology, 2019)
Heavy metals are non-biodegradable substances which cause serious carcinogenic effects on animals and humans. As fish occupy top position of aquatic food chain, it is a major source of heavy metal contamination. The concentration of Cd, Cr, Pb, Mn, Fe, Cu, and Zn were 0.0156 - 0.1428, 0.163 - 8.53, 0.0924 - 0.4026, 9.38 - 65.9382, 0.0473 - 0.1981 and 0.1473 - 1.8148 ppm respectively for the fish samples of Cox’s Bazar region while 0.0191 - 0.1386, 0.8445 - 0.1743, 0.102 - 0.4625, 0.102 - 0.4675, 9.7269 - 60.5267, 0.3108 - 0.046 ppm for the fish samples of Saint Martin’s region. Comparatively high concentrations of heavy metals were found to be accumulated in Mola (Amblypharyngodon mola), Rupchanda (Stromateus chinensis) and Chhuri (Trichiurus lepturus). The order of heavy metal concentrations were Fe > Zn > Cr > Cu > Mn > Cd. The concentration of heavy metals varied from species to species and most of the metals were not significantly correlated, even some metals showed negative correlation among them. Concentration of Fe in some fishes (Mola, Rupchanda and Chhuri) was found higher than WHO guideline values, while other metals exhibited the value below the WHO standard. The results of this study will assist in acquiring information about the level of toxic metals in these regions and to improve the coastal management in these areas in future. Bangladesh J. Zool. 47(2): 293-304, 2019